Advanced targeted nanomedicines for vulnerable atherosclerosis plaque imaging and their potential clinical implications - Li, Xue; Wu, Menglin; Li, Jiang; Guo, Qi; Zhao, Yang; Zhang, Xuening (Frontiers in Pharmacology, 2022)
Atherosclerosis plaques caused by cerebrovascular and coronary artery disease have been the leading cause of death and morbidity worldwide. Precise assessment of the degree of atherosclerotic plaque is critical for predicting the risk of atherosclerosis plaques and monitoring postinterventional outcomes. However, traditional imaging techniques to predict cardiocerebrovascular events mainly depend on quantifying the percentage reduction in luminal diameter, which would immensely underestimate non-stenotic high-risk plaque. Identifying the degree of atherosclerosis plaques still remains highly limited. vNanomedicine-based imaging techniques present unique advantages over conventional techniques due to the superior properties intrinsic to nanoscope, which possess enormous potential for characterization and detection of the features of atherosclerosis plaque vulnerability. Here, we review recent advancements in the development of targeted nanomedicine-based approaches and their applications to atherosclerosis plaque imaging and risk stratification. Finally, the challenges and opportunities regarding the future development and clinical translation of the targeted nanomedicine in related fields are discussed.